Inventing the "Great Awakening" - Lambert, Frank, 1943- (Princeton, N.J. : Princeton University Press, 1999)
This book is a history of an astounding transatlantic phenomenon, a popular evangelical revival known in America as the first Great Awakening (1735-1745). Beginning in the mid-1730s, supporters and opponents of the revival commented on the extraordinary nature of what one observer called the "great ado," with its extemporaneous outdoor preaching, newspaper publicity, and rallies of up to 20,000 participants. Frank Lambert, biographer of Great Awakening leader George Whitefield, offers an overview of this important episode and proposes a new explanation of its origins
Opening Events: The "Great Awakenings" of the 1730s -- " ... that Religion may review in this Land" -- Revival Traditions -- "In Such an Age as This" -- Declaring the Acceptable Year of the Lord -- "the first fruits of this extraordinary and mighty Work of God's Special Grace" -- Revival in New Jersey -- Awakening in the Connecticut Valley -- A Faithful Narrative: The Northampton Revival as Told ... and Retold -- Wider Connections: An Intercolonial Great and General Awakening, 1739-1745 -- "imported Divinity" -- George Whitefield and Revivalism in England -- "We Hear From Abroad": News of the English Evangelical Revival -- Why 1739? -- Promoting Whitefield in the Colonies -- The "Revival at ..." -- Local and Regional Dimensions -- Revival Narratives: A Common Script -- " ... similar facts ... are now united": Constructing a Transatlantic Awakening -- British-American Revival Networks -- Revival Magazines: "The Progress of the Gospel in England, Wales, Scotland, and America" -- Historical Connections: The Great Awakening in Salvation History -- Contested Inventions, 1742-1745 -- The "grand delusion" or "great Mistakes of the present Day" -- The Revival as Artifice -- Antirevivalist Message -- Antirevivalist Publications -- "This is the Lord's Doing" -- Apologies: Defending the Revival as the Work of God -- Polemics: Attacking Opponents of the Work of God -- Differentiation: Distinguishing the Work of God from Enthusiasm -- Epilogue. "The late Revival of Religion."
Includes bibliographical references (pages 281-293) and index.
Print version record.
JSTOR
Keywords: Great Awakening; Revivals -- New England -- History -- 18th century; Revivals -- New Jersey -- History -- 18th century; Grand Réveil.; Réveils (Religion) -- Nouvelle-Angleterre -- Histoire -- 18e siècle.; Réveils (Religion) -- New Jersey -- Histoire -- 18e siècle.; 11.59 church history, history of doctrine: other; 15.85 history of America; HISTORY -- United States -- Colonial Period (1600-1775); Great Awakening; Revivals; New England; New Jersey; The Great Awakening; Great Awakening; Great Awakening; Revivals -- New England -- History -- 18th century; Revivals -- New Jersey -- History -- 18th century; Geschichte 1730-1745.; 1700-1799; Acts of the Apostles; Antinomianism; Baptists; Boston; Bristol; Calvinism; Concert for Prayer; Congregationalists; Cross, Robert; Cummings, Archibald; Davidson, Henry; Deism; Dickinson, Jonathan; Edinburgh; Edwards, Timothy; Enlightenment; Fielding, Henry; Foxcroft, Thomas; Gentleman's Magazine; Glasgow Weekly History; Gooch, William; Hamilton, Dr. Alexander; Historical Collections; Huguenots; Independents; Kilsyth, Scotland; London Gazette; Mather, Increase; New Lights; New York Gazette; Nova Scotia; Old Lights; Parkman, Ebenezer; Pentecost; Pietism; Quakers; Ramism; bank war; church census; conversion narratives